The role of the trees origin in the formation of radial growth of oak (Quercus robur L.) in the Ukrainian Western Forest-Steppe - Novak, A. A.; Vytseha, R. R. (Forestry and Forest Melioration, 2021)
Introduction The radial growth of both individual trees and stands as a whole is, according to some scientists, the most integrated and comprehensive indicator that reflects their growth conditions, health, and response to adverse environmental factors. Materials and Methods Features of oak (Quercus robur L.) radial growth formation in stands of different origins were studied within Western Forest-Steppe in Ukraine. The stands in which the sample plots were laid out and samples of tree-ring chronologies were selected had natural seed origin, artificial seed (forest crops), and natural vegetative (first generation) origin. In the study, standard statistical and dendrochronological methods were used. Quantitative indicators such as average annual growth rate, the scope of its variation, standard deviation, and coefficient of variation have been calculated. Analytical results on autocorrelation of chronological series, its sensitivity, and synchronicity were used to identify the influence of exogenous and endogenous factors on the formation of radial growth of English oak in the Western Forest-Steppe. Results Artificially seeded stands had a higher average annual growth rate than naturally seeded ones. Vegetative stands were marked by the highest rate of average annual growth. There is no significant difference in the origin of stands by the standard deviation. The variability of the growth series indicates moderate structural and functional changes in the ring series of stands of different origins. The highest coefficient of variation is characteristic of vegetative natural forests. All ring series show low sensitivity to external factors, although the value of the sensitivity coefficient of the ring series of vegetative stands is more sensitive than of seeded ones. Autocorrelation of chronological series is closer and longer in naturally seeded stands. Stands of vegetative origin show weak and short-lived autocorrelation. The results of the cluster analysis are expected to demonstrate the similarity of the chronological series of seed stands of natural and artificial origin. Vegetative stands show significant differences in the nature of radial growth formation. Conclusions Artificial seed stands have a larger average annual growth than those of natural seed origin. Vegetative stands are marked by the highest rate of average annual growth. When studying the variability of dendrological series by the magnitude of the standard deviation, a significant difference in the origins of stands is not observed. The variability of the growth series indicates moderate structural and functional changes in all stands. All stands show low sensitivity to external factors, although the vegetative stands were found to be more sensitive than seeded ones. Autocorrelation of chronological series is closer and longer in naturally seeded stands. Stands of vegetative origin show weak and short-lived autocorrelation. The highest synchronicity of ring chronological series is demonstrated by seed stands. Annular chronological series of artificially seeded and vegetative stands are characterized by the lowest synchronicity. On the basis of cluster analysis, the similarity between the chronological series of seed stands of natural and artificial origin is proved. Vegetative stands show significant differences in the formation of radial growth.